Worchitect: an English grammar (parts of speech) card game / Adi Idham Jailani ... [et al.] - Jailani, Adi Idham; Razali, Nazarul Azali; Md Yusuf, Ahmad Harith Syah; Anuar Yatim, Ariff Imran Anuar Yatim; Mohamad, Nor Atifah (Universiti Teknologi MARA, 2018)
Mastery of the English grammar is an intricate subject. Conventional teaching and learning of the English grammar have found to be an arduous task for teachers and a lacklustre one for students. The traditional pen and paper method often cause second language (L2) learners to become unmotivated in understanding this important element of the language. Thus, it is critical to provide L2 learners with the motivation to engage learning grammar in a more meaningful and purposive process. An ideal way to provide such learning experiences is through the use of language games that accommodate L2 learners' desire to grasp grammar rules in an enjoyable way. To fill the gap for a purposive and meaningful grammar-based language game, Worchitect, a card-based game that focuses on (English) parts of speech is developed. The card game poses players/learners with questions that will foster their understanding of the rules of grammar for them to play the game and accumulate the highest scores possible. This game provides a constructive reinforcement to L2 users as it allows for the English parts of speech (and grammar) rules to be deductively attained. Furthermore, Worchitect is highly marketable as it is suitable for learners of various language proficiencies; for language teachers to be used as reinforcement or the actual learning activity; for parents who are looking to spend quality time with their children; and for any language enthusiast.